Google's Sustainable Business Strategy: Synthesis of the 5Ps Framework, Creating Shared Value, ESG, and SDGs - Fonny Arisandy Jacob; Mohamad Rizan; Muhammad Awaluddin (Journal of Digital Business and Global Economy, 2026)
This paper aims to describe Google's sustainable business strategy as a single, document-based case study. This study uses a descriptive qualitative approach with a documentary case study method, analyzing the Google Environmental Report 2026 as the main source of cases, complemented by supporting academic literature. Five analytical lenses are used in an integrated manner to describe the strategy, namely Henry Mintzberg's 5Ps of Strategy, Deliberate Strategy and Emergent Strategy, Porter and Kramer's Creating Shared Value, and ESG and SDGs frameworks. The results show that Google's sustainability strategy includes large-scale clean energy procurement, supply chain transformation, circular product innovation, and structured sustainability governance. In terms of emissions, Google reported a 3% decrease in Scope 2 emissions, while Scope 1 and Scope 3 emissions increased by 20% and 25%, respectively, in the same reporting period. This research contributes to providing an integrated picture of how the five frameworks can be used together to describe the sustainability strategy of a global technology company.